Analysis of hydraulic characteristics of fluid multiplier fish pump based on CFD simulation. (15th March 2023) - Liu, Andong; Zhang, Chenglin; Zhang, Yulei; Zhang, Yufei
Abstract: The fish pump is an important power component for aquaculture, especially in offshore engineering vessel aquaculture and cage aquaculture. Reducing fish damage, improving survival rate, and increasing fish-lifting efficiency are the key points of fish pump research. In this study, we took a new type of fluid multiplier fish pump as the research object and selected many performance parameters that affect the hydrodynamic performance of the model prototype of the fish pump. The main conclusions are as follows: the fluid multiplier fish pump body produced a flow rate 2.8–3.5 times higher than the water injection port in the jet gap area, and under the influence of the high-flow-rate area, the low-pressure area generated at the fish inlet amplified the flow at the entrance of the fish. As a result, the fluid multiplier fish pump was able to suck and lift fish. With the change in the water jet gap from 2 mm to 4 mm, the head and flow of the bladeless fish pump were improved to a certain extent. We achieved an optimal value for the runner inclination angle during the change of the inclination angle of the pump body surface from −4° to 4°, and it reached the highest value when the inclination angle was 2°. In the process of increasing the water injection opening of the pump body from 50 mm to 65 mm, the head and flow of the bladeless fish pump greatly increased. The flow when the water injection opening was 65 mm was approximately 1.71 times that when the water injection opening was 50 mm. The head when the water injection opening was 65 mm was approximately 1.42 times that when the water injection opening was 50 mm. When the length of the guide vane was between 4 and 6 mm, the increase and decrease in the flow rate of the bladeless fish pump approached the maximum value of merit. The fluid multiplier fish pump designed in this study featured the characteristics of simple and lightweight structure and high fish-lifting flow, which can reduce labour intensity and improve the catching efficiency of aquaculture fish. Highlights: A concept of a new bladeless fish pump using fluid multiplication technology is proposed. The actual working performance of the bladeless fish pump are tested by making a prototype and conducting field tests. The influence of structural parameters on the hydrodynamic performance of the fish pump model is analyzed. A method to reduce the damage rate of the fish body is proposed by using the structure designed by the Coanda effect.